2021
DOI: 10.3324/haematol.2021.280163
|View full text |Cite
|
Sign up to set email alerts
|

Antibody response after vaccination against SARS-CoV-2 in adults with hematological malignancies: a systematic review and meta-analysis

Abstract: Vaccines against SARS-CoV-2 have shown remarkable efficacy and thus constitute an important preventive option against COVID-19, especially in fragile patients. We aimed to systematically analyse the outcomes of patients with haematological malignancies who received vaccination and to identify specific groups with differences in outcomes. The primary end point was antibody response after full vaccination (two doses of mRNA or one dose of vector-based vaccines). We identified 49 studies comprising 11086 individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
84
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(90 citation statements)
references
References 69 publications
(23 reference statements)
6
84
0
Order By: Relevance
“…Our study showed that the proportion of patients achieving a serologic response after a single or two doses of COVID-19 vaccine was 54% and 88%, respectively, which are much lower than the rates reported by Shroti et al Among studies that included control patients without cancer, the OR of achieving serologic response among patients with cancer was significantly lower after the first and second dose. The results of our study are consistent with recent meta-analyses reporting lower response rates in hematological cancers vs. solid cancers or controls [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…Our study showed that the proportion of patients achieving a serologic response after a single or two doses of COVID-19 vaccine was 54% and 88%, respectively, which are much lower than the rates reported by Shroti et al Among studies that included control patients without cancer, the OR of achieving serologic response among patients with cancer was significantly lower after the first and second dose. The results of our study are consistent with recent meta-analyses reporting lower response rates in hematological cancers vs. solid cancers or controls [ 42 , 43 ].…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with previous studies, our NHL patients generate poor antibody responses upon COVID vaccine administration, with a more pronounced deficiency detected after exposure to rituximab [18] , [19] , [20] , [21] , [22] . Our data demonstrates that poor seroconversion rates occur concomitantly with severe B-cell cytopenia, which is most severe within the first year post rituximab.…”
Section: Discussionsupporting
confidence: 91%
“…Overall, most literature evidence on healthy individuals describes a significant reduction of antibody levels four-six months after the second COVID-19 vaccine dose. Fragile patients, such as patients with haematological malignancies and haemodialysis, show an overall reduced response to anti-SARS-CoV-2 vaccination than healthy individuals 26 , 27 . Additionally, some Authors reported that fragile patients have a significantly more substantial decline of anti-SARS-CoV-2 antibody titers within 6 months compared to healthy individuals 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%